تأثير الذكاء العاطفي على النية المقاولاتية دراسة ميدانية على طلبة السنة الثالثة إدارة أعمال جامعة محمد خيضر بسكرة: The effect of emotional intelligence on entrepreneurial intention, a field study on the third year students of the 3 LMD at the University of Biskra - وفاء رايس (Journal of North African Economies, 2025)
The study aimed to show the extent to which emotional intelligence has an impact on the intention of conducting a field study on a sample of third-year students managing the work of the University of Biskra, and how it can affect their intention to engage in this type of activity after graduation. As a tool for collecting data and trying to process it and then analyzing it statistically and sociologically using appropriate statistical programs, the most prominent finding of the study was the existence of a statistically significant effect of emotional intelligence on the entrepreneurial intention of the study sample, and there is no statistically significant effect for both the evaluation and expression of emotions as well as the regulation of emotions on the entrepreneurial intention, and the presence of an impact of a brainThe researcher recommended the need to spread the culture of awareness of the importance of the variables of study emotional intelligence, the intention of contracting among university students, the training of university students through holding seminars, scientific conferences and training programs on this subject and encouraging students to participate in these meetings, with the aim of developing their intelligence skills and evaluating the results of these programs through continuous field followup, as well as the need to review the strategy of contracting to include a culture of emotional intelligence and work. to be established among students.